Hereditary protein C deficiency with recurrent thrombosis: identification of a missense mutation (C6218T). - Song, K. S. (Korean Academy of Medical Sciences, 1998)
Protein C is the central component of a major anti-thrombotic regulatory system and individuals with hereditary protein C deficiency (PCD) tend to have an increased risk of thromboembolism. During the last several years, mutations causing PCD have been identified in Western countries and in Japanese. In the present study, we report a case of hereditary PCD with a missense mutation (C6218T) in a 44 year old female with recurrent pulmonary thromboembolism. The protein C activity (35%) and antigen (58%) levels in this patient were decreased. Furthermore, we have identified the same molecular defect and PCD in other asymptomatic family members including proband's mother and two daughters and one son. To our knowledge, this is the first case of hereditary PCD with identified genetic defect in the Korean population, which may be one of hot spots for mutation in the protein C gene.